Regulatory roles of tRNA-derived RNA fragments in human pathophysiology - Kush Kumar Pandey; Deeksha Madhry; Y.S. Ravi Kumar; Shivani Malvankar; Leena Sapra; Rupesh K. Srivastava; Sankar Bhattacharyya; Bhupendra Verma (Elsevier, 2021)
Hundreds of tRNA genes and pseudogenes are encoded by the human genome. tRNAs are the second most abundant type of RNA in the cell. Advancement in deep-sequencing technologies have revealed the presence of abundant expression of functional tRNA-derived RNA fragments (tRFs). They are either generated from precursor (pre-)tRNA or mature tRNA. They have been found to play crucial regulatory roles during different pathological conditions. Herein, we briefly summarize the discovery and recent advances in deciphering the regulatory role played by tRFs in the pathophysiology of different human diseases.